Case Report: Infective Endocarditis Caused by Aspergillus flavus in a Hemodialysis Patient - Dai, Tingting; Hu, Qinghua; Xie, Zhongshang; Li, Chunhui (Frontiers in Medicine, 2021)
Fungal endocarditis (FE) is a rare but fatal disease. The incidence of infective endocarditis (IE) in hemodialysis patients with catheters is thought to be obviously higher than that in the general population. We reported a case of IE caused by Aspergillus flavus (A. flavus) in a 36-year-old woman on hemodialysis. Because the blood cultures were persistently negative, so we used mNGS(Metagenomic next generation sequencing) for early clinical diagnosis. After treatment with voriconazole, the patient's condition improved rapidly. She continued oral voriconazole treatment one year after discharge and is in good condition. The diagnosis and treatment strategies of FE in hemodialysis patients were discussed.